Accounting and Fraud Curriculum from The Perspective of Islamic Law - Junaidi Junaidi (JAFFA, 2024)
Hudud's thinking aims to provide an alternative answer to the relative failure of developing the accounting curriculum in anticipation of accountant malpractice. Efforts to improve and develop the accounting curriculum, changes in accounting standards, forensic accountant certification, considerable data utilization and more have been undertaken in anticipating accountant malpractice. After graduating accounting students work, but the structure of the accountant (the other) is less successful in negotiating when dealing with clients (the power) while working. Accountants understand that being part of an act of theft of stored goods through science and technology can destroy the universe. The Qur'an provides a reference to avoid theft through education. The result concludes that Islamic law regarding Hudud should be passed on by educators to the learners in an accounting course.